HOME INDUSTRY - PEMANFAATAN BAHAN TANAMAN UNTUK PEMBUATAN SISTEM PENJERNIHAN AIR - Wijayanto, Teguh; Rakian, Tresjia C.; Asniah, Asniah; Rahni, Nini Mila; Hisein, Anima; Dedu, La Ode Arfan (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
This Community Service Program has been implemented in Kambu Village, Kambu District, Kendari, Southeast Sulawesi, with the target audience, especially the Housewife Group. Like other areas near the sea coast, problems with the availability of clean water and pollution of water sources often occur, including those often faced by the community in Kambu Village, Kendari. The solution and target offered was to carry out outreach and technical guidance as well as a demonstration of developing a simple water purification system, using natural coagulants from plants or plant residues and other local resources, which can be easily obtained in our environment, including Moringa oleifera seed powder or banana peels, as an alternative source of organic coagulant for absorption, agglomerates and neutralizes the surface tension of mud particles and heavy metals contained in waste substances. This service activity was carried out through method stages: socialization (technical guidance and discussion), demonstration and application of appropriate technology for water purification based on local resources, as well as mentoring. This service activity was carried out by actively empowering the target group through outreach activities, demonstrations and technical guidance. The results of service activities showed: 1) the importance of establishing work programs and implementing science and technology that were in accordance with the needs and conditions that exist in the target community; 2) the implemented work program received a very good response, response and attention from the community and local government officials; 3) the community was greatly helped and gains additional knowledge and skills by implementing appropriate technological innovations; 4) with this service program the relationship between higher education institutions as a source of knowledge with the community and local government improved